Dialektika Islam dan Ilmu Pengetahuan Studi Waḥdat al-‘Ulūm Menurut al-Ghazali - Usman, Mohammad (LPPM, 2020)
Abstract: The dichotomy of sciences caused both the positive and negative effects for development of civilizations; such as poverty, economic colonialism and dehumanization. Therefore, the unity of sciences is an interesting and important to be discussed for developing a new and prosperous civilization. This paper discussed the unity of sciences according to Imam al-Ghazali (d. 1111) and its urgency to the issue of human life. For al-Ghazali, science must be unified in the aspects of ontology, epistemology, and axiology. These three aspects of knowledge united in one entity; such as three angles in a triangle. From the pespective of ontology, knowledge comes from God and cannot be separated from God, so all sciences are commendable. Epistemologically, the nature of science is the light coming from the illumination light of God. Science can be obtained by optimizing the function of reason and through revelation or inspiration. The validity of science is depended on how and sources used to obtain it. Knowledge is not for knowledge, but knowledge for human prosperity. To realize the concept of the unity of sciences it is needed a hard work, patience and many-stage processes; namely equal treatment on scientific and religious knowledge, dialogue, integration and interconnection between science and the end is the unity of sciences.